2003
DOI: 10.1093/geronb/58.1.s38
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and Acute Care Utilization

Abstract: Lower cognitive function may be a barrier to outpatient care, but these analyses should be repeated using administrative use and cost data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 23 publications
5
46
1
Order By: Relevance
“…On the one hand, subclinical status in lower body function may serve as an access barrier for physician visits, and less frequent physician use may reduce the risk of hospitalization. On the other hand, the onset of (or increases in) difficulties with ADLs (especially those that are more cognitively demanding) initially increases the demand for health services (reflecting diagnostic and evaluation activity), followed by a triage and selection process (associated with forgoing subsequent treatment) after recovery is deemed unlikely (24)(25)(26)(27)(28)(29)(30). In this study of middle-aged adults, it is unlikely that the initial increase in service demand has given way to the triage and selection processes.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, subclinical status in lower body function may serve as an access barrier for physician visits, and less frequent physician use may reduce the risk of hospitalization. On the other hand, the onset of (or increases in) difficulties with ADLs (especially those that are more cognitively demanding) initially increases the demand for health services (reflecting diagnostic and evaluation activity), followed by a triage and selection process (associated with forgoing subsequent treatment) after recovery is deemed unlikely (24)(25)(26)(27)(28)(29)(30). In this study of middle-aged adults, it is unlikely that the initial increase in service demand has given way to the triage and selection processes.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, previous studies have been restricted to the relationship between cognitive function and acute care utilization [13][14][15] , or medications and outpatient services [16] . Cognitive impairment was associated with increased hospital and emergency room use, and lower cognitive functioning reduced the use of medication and outpatient services.…”
mentioning
confidence: 99%
“…Previous studies have found that income and social support are associated with health service use [16,17], especially in patients with dementia [18]. However, to the authors' knowledge, no studies have evaluated the effect of financial problems and social network on MCD individuals' use of GP services.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has found no association between cognitive decline and contact with a GP [5,19,21]. Finally, there is research which shows that cognitive impairment is associated with fewer visits to GPs [17]. …”
Section: Introductionmentioning
confidence: 99%